Study of amino acids absorption and gut microbiome on consumption of pea protein blended with enzymes-probiotics supplement - Rathi, Abhijit; Gaonkar, Tejal; Dhar, Debojyoti; Kallapura, Gopalakrishna; Jadhav, Swati (Frontiers in Nutrition, 2024)
The current randomized, double-blind, crossover clinical trial was conducted to evaluate changes in the amino acids absorption and gut microbiota on consumption of pea protein supplemented with enzymes-probiotics blend (Pepzyme Pro). 15 healthy subjects were instructed to take test (pea protein + Pepzyme Pro) or placebo (pea protein + maltodextrin) for 15 days with 30 days of washout period. Blood samples were analysed for plasma free amino acids, insulin, and C-reactive protein (CRP). Additionally, nitrogen levels in urine and faeces, along with the composition of gut microbiota were evaluated. On day 15, test arm showed tendency to increase rate of absorption and total absorption (AUC) of amino acids compared to the placebo arm, though the increase was statistically insignificant. In addition, 15 days test supplementation showed tendency to reduce Tmax of all the amino acids (statistically insignificant except alanine, p=0.021 and glycine, p=0.023) in comparison to the placebo supplementation. There were no changes in urine and faecal nitrogen levels as well as serum CRP levels in the test and placebo arm. The increase in serum insulin level after 4h was statistically significant in both the arms, whereas the insulin level of placebo and test arm at 4h was not statistically different. Supplementation showed changes with respect to Archea and few uncharacterized species but did not show statistically significant variations in microbiome profile at the higher taxonomic levels. A study with large sample size and detailed gut microbiome analysis is warranted to confirm the results statistically as well as to characterize altered species. However, the current study could provide inkling of positive alteration in protein digestibility, amino acid absorption, and gut microbiome on regular consumption of protein and enzymes-probiotics blend.